Germany and the United Kingdom: Under the shadow of the great decoupling - Mieta Bobanović (UTMS Journal of Economics, 2021)
New challenges arise with the trends that the Industrial revolution brings, as well as the impacts of Globalisation which are inextricably intertwined. Experts in the field are working together on creating tools in order to predict the domino effect it may cause to the economy. It is known that technology plays a defining role in creating opportunities but also risks on a global scale. The Great Decoupling, a study on the US and in the focus of Brynjolfsson and McAfee (2013), suggests that wages do not grow in union with productivity as it used to. To understand better this phenomenon, an adapted model of the Great Decoupling will be applied the case of Germany and United Kingdom as Europe's strongest economies. The two means tests between the growth rates of each variable will be conducted and results discussed.
Keywords: A10; O03; O04; 330; Great Decoupling; economic growth; Germany; United Kingdom; productivity